Soil classes for oil palm in southeast Bahia state, Brazil - Leão, Antônio Carlos (Pesquisa Agropecuaria Brasileira, 2014)
Oil palm (Elaeis guineensis Jacquin) is cultivated in Malaysia, lndonesia and many tropical countries of the african and american continents. Although it is grown in different soil types, there are evidences that within certain climatic conditions, variations of the physical and chemical soil properties can cause significant differences in its production. Based on the knowledge of the root system morphology of this plant and of its climatic and edaphic requirements, the physical and chemical parameters of the soil, agreed to be more important for its growth and yield, were specified. For each physical and chemical parameter selected, three serviceable grades were defined for appropriate oil palm cultivation: favourable, little favourable and unfavourable. The soil classes for oil palm were defined in accordance to the serviceable grades of these parameters, in: good, regular, marginal and inadequate. Fertility grades established from chemical characteristics allowed the separation of these classes into subclasses. According to the methodology used, southeast Bahia, Brazil, with and area of 90,000 km 2, has 56,8% of marginal soils, 17,5% of good sofis, 13,7% of regular soils and 12,0% of inadequate soils for oil palm cultivation